Newborn-Care Training and Perinatal Mortality in Developing Countries - Carlo, Waldemar A. (2010)
BACKGROUND: Of the 3.7 million neonatal deaths and 3.3 million stillbirths each year, 98% occur in developing countries. An evaluation of community-based interventions designed to reduce the number of these deaths is needed. METHODS: With the use of a train-the-trainer model, local instructors trained birth attendants from rural communities in six countries (Argentina, Democratic Republic of Congo, Guatemala, India, Pakistan, and Zambia) in the World Health Organization Essential Newborn Care course (which focuses on routine neonatal care, resuscitation, thermoregulation, breast-feeding, "kangaroo" [skin-to-skin] care, care of the small baby, and common illnesses) and (except in Argentina) in a modified version of the American Academy of Pediatrics Neonatal Resuscitation Program (which teaches basic resuscitation in depth). The Essential Newborn Care intervention was assessed among 57,643 infants with the use of a before-and-after design. The Neonatal Resuscitation Program intervention was assessed as a cluster-randomized, controlled trial involving 62,366 infants. The primary outcome was neonatal death in the first 7 days after birth. RESULTS: The 7-day follow-up rate was 99.2%. After birth attendants were trained in the Essential Newborn Care course, there was no significant reduction from baseline in the rate of neonatal death from all causes in the 7 days after birth (relative risk with training, 0.99; 95% confidence interval [CI], 0.81 to 1.22) or in the rate of perinatal death; there was a significant reduction in the rate of stillbirth (relative risk with training, 0.69; 95% CI, 0.54 to 0.88; P=0.003). In clusters of births in which attendants had been randomly assigned to receive training in the Neonatal Resuscitation Program, as compared with control clusters, there was no reduction in the rates of neonatal death in the 7 days after birth, stillbirth, or perinatal death. CONCLUSIONS: The rate of neonatal death in the 7 days after birth did not decrease after the introduction of Essential Newborn Care training of community-based birth attendants, although the rate of stillbirths was reduced. Subsequent training in the Neonatal Resuscitation Program did not significantly reduce the mortality rates. (ClinicalTrials.gov number, NCT00136708.)